The Role of Vaccination in Prevention of Foodborne Disease in Children: A Systematic Review - Manullang, Frenky Sorimuda; Anto, Endy Juli (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Foodborne diseases pose a significant global health challenge, particularly for children in developing countries. Vaccination has emerged as a crucial strategy in controlling these diseases. This review examines the effectiveness and safety of foodborne disease vaccines in children based on recent literature. Subjects and Method: This systematic review was conducted using Google Scholar, PubMed, and WHO websites with the keywords